Evaluasi Tingkat Pemahaman Pelatih di Kota Surabaya terhadap Atlet Kelas Festival dan Prestasi dalam Cabang Beladiri Taekwondo - Feni Indrayani; Soni Sulistyarto; Made Pramono; Hijrin Fithroni (Journal of Creative Student Research, 2024)
The role of the coach is very influential in producing competent athletes. The coach acts as a guide for the athlete to achieve the expected targets. Coaches at least understand what the concept of training is and the stages that athletes must go through before becoming elite athletesThis research aims to determine the level of understanding of Taekwondo Martial Art Coach in Surabaya City regarding festival and elite class athletes. This research is based on the results of the Level 1 Regional coach Training test for the sport of Taekwondo. The results of this research were obtained from the Regional Coach Training Level 1 which was attended by Taekwondo Coach throughout East Java, however the researcher will only analyze the test results from coach who live in Surabaya City. The number of sample values ​​obtained came from 100 coach, both main trainers and assistant trainers. The assessment aspects taken in Level 1 Coach Training come from various tests carried out by several presenters. The material that will be included in the test assessment is Competition Rules for both the Kyorugi (Competing) and Poomsae (Art) categories, strength and conditioning, Kyorugi and Poomsae athlete fundamentals, LTAD (Long Term Athlete Development), Prevention and treatment of injuries in sports. The match competition rules tested refer to the latest rules used by the World Taekwondo Federation (WTF). The results of the pre-test and post-test showed an increase which could mean that the coach understood the material provided.